A Dr: Pengaruh Model Pembelajaran Gerak Dasar Lokomotor Berbasis Augmented Reality Terhadap Hasil Belajar Pada Mata Pelajaran Penjasorkes Di Sekolah Dasar Negeri 3 Banjar jawa Buleleng - Budiadnyana, Budiadnyana; Ngurah Putra Laksana, Anak Agung; Riesa Mahendradhani, I Gusti Ayu Agung (Universitas Singaperbangsa Karawang, 2024)
The development of basic movements and their perfection is important during elementary school age. Physically active children have reduced risks of excessive weight gain, cardiovascular disease, osteoporosis and type 2 diabetes, as well as favorable psychological and emotional benefits such as improved mental health, higher self-esteem and better emotional self-efficacy . The aim of this research is to produce and test whether an augmented reality-based model of the influence of basic movement training advertisements is available and whether it can improve basic movement learning outcomes in physical education subjects. The method used in this research is an experimental research method l. Meanwhile, the research design used was a pre test-post test control group design. The subjects of this research were year-old students including at SDN 3 Banjar Jawa, grade 4 students as the experimental group and grade 5 students as the control group. The instruments used in the research are: Motor Growth Test, 2) walking 10 meters for locomotor. Data analysis in this study used the paired sample t-test statistical method and the results showed that the influence of this learning model was significant in improving basic movement learning for students aged 7 -9 years, the second compares with the control group. The results of statistical tests show that the basic movement learning model developed in the experimental group is more effective compared to the control group which used conventional learning models. The analysis was carried out using an independent t-test to determine the difference in results between the control and experimental groups. It was obtained that the difference in t-count = 8.988, with df = 30 and a sig or p-value = 0.000 which was smaller than the alpha value of 0.05. Based on these results, it can be decided to reject H0. Thus, it can be concluded that there is a difference in the quality of learning between the control group and the experimental group. The findings of this research are the training models and test instruments that have been developed. This learning model is packaged in the form of a printed book, an augmented reality Android application in the form of an ebook and an Android application containing 3-dimensional characters implementing variations of learning basic movements.